Numerical study of the spray impingement onto a solid wall - Rodrigues, Christian Michel Gomes (2011)
The modelling of turbulent multiphase flows has been gathering high interest in the last decades in the scientific community due to its relevance in several applications, such as in industrial and environmental processes or for chemical and biomedical purposes. In fact, regarding the industrial applications, the impingement of liquid fuel sprays onto engine surfaces has become a subject of interest due to its influence on the mixture preparation prior to combustion and, consequently, engine performance and pollutants emission (Barata and Silva, 2005). However, there is still a lack of knowledge concerning the spray-wall interaction but also concerning the exact phenomenon occurring during the process. These gaps do not allow defining the most favourable conditions for the optimal engine performance. Hence, the main challenge for the investigators lies in attaining a much deeper understanding of the phenomena involved in the spray impingement process, through either theoretical analysis or experimental investigation. Meanwhile, the splash phenomenon has been the focus of many researchers due to its relevance in the combustion process of small-bore, direct-injected gasoline and diesel engines, as well as in a variety of other industrial devices in which sprays impinge on solid surfaces. Bai and Gosman (1995) developed a model to predict the outcomes of spray droplets impacting on a wall with temperatures below the fuel boiling point. This model, which has been formulated using a combination of simple theoretical analysis and experimental data from a wide variety of sources, was later improved (Bai et al., 2002) by refining the dissipation energy term and by enhancing the post-splashing characteristics. In fact, recently, significant attention has been given to this regime either through the definition of transition criteria that better fit specific conditions of the experimental configuration under study or by characterizing the behaviour of the drop during all stages of the regime (expansion of the lamella, crown formation and propagation, etc.) through both theoretical analyses and experimental data. Beyond the transition criteria, another aspect that controls the characteristics of the secondary droplets after the impacts is the energy dissipation term and thus, it is essential its proper definition for adequately modelling these multi-phase flows. However, contrary to spreading, there is little literature available related to this particular parameter and, more important than that is the fact that there is a certain ambiguity even for what it represents exactly. In addition, the majority of the dissipative energy loss relationships have been deduced for the spread regime, i.e., from the beginning of the expansion of the lamella until the drops reaches its maximum extent (without splashing). This situation can be overcome through some simplifying assumptions, which obviously carries inaccuracy. The present work is dedicated to the study of the sprays impingement onto a solid wall through a crossflow. The major purpose of the thesis is to improve the accuracy of the base model, which is the model of Bai et al. (2002), through the employment of both new correlations for the deposition/splash transition criteria and energy dissipation loss relationships available in the literature. The numerical predictions are then compared with the experimental data of Arcoumanis et al. (1997) for two crossflow rates ( and ). From the results, it can be concluded that the employment of different transition criteria can bring better results (see also Silva et al., 2011). On the other hand, no improvements were seen by the employment of the new energy dissipative loss relationships in the base models, which calls for further research in this particular matter.